Mutant MRPS5 affects mitoribosomal accuracy and confers stress‐related behavioral alterations. (20th September 2018) - Akbergenov, Rashid; Duscha, Stefan; Fritz, Ann‐Kristina; Juskeviciene, Reda; Oishi, Naoki; Schmitt, Karen; Shcherbakov, Dimitri; Teo, Youjin; Boukari, Heithem; Freihofer, Pietro; Isnard‐Petit, Patricia; Oettinghaus, Björn; et al.
Abstract: The 1555 A to G substitution in mitochondrial 12S A‐site rRNA is associated with maternally transmitted deafness of variable penetrance in the absence of otherwise overt disease. Here, we recapitulate the suggested A1555G‐mediated pathomechanism in an experimental model of mitoribosomal mistranslation by directed mutagenesis of mitoribosomal protein MRPS5. We first establish that the ratio of cysteine/methionine incorporation and read‐through of mtDNA‐encoded MT‐CO1 protein constitute reliable measures of mitoribosomal misreading. Next, we demonstrate that human HEK293 cells expressing mutant V336Y MRPS5 show increased mitoribosomal mistranslation. As for immortalized lymphocytes of individuals with the pathogenic A1555G mutation, we find little changes in the transcriptome of mutant V336Y MRPS5 HEK cells, except for a coordinated upregulation of transcripts for cytoplasmic ribosomal proteins. Homozygous knock‐in mutant Mrps5 V338Y mice show impaired mitochondrial function and a phenotype composed of enhanced susceptibility to noise‐induced hearing damage and anxiety‐related behavioral alterations. The experimental data in V338Y mutant mice point to a key role of mitochondrial translation and function in stress‐related behavioral and physiological adaptations. Synopsis: An experimental model of mitochondrial mistranslation based on the mutation V336Y in mitoribosomal protein MRPS5 recapitulates the suggested pathomechanism of the A1555G mutation in mitochondrial 12S rRNA. Accuracy of mitochondrial protein synthesis can be assessed by in organello translation of MT‐CO1. Mutation V336Y in MRPS5 confers mitoribosomal misreading. MRPS5 V336Y knock‐in mice reproduce the hearing‐related deficit in the absence of non‐cochlear pathology that characterizes the A1555G mutation. Further assessment of the in vivo model points to a key role for mitochondrial function in behavioral and physiological adaptations. Abstract : Mitochondrial mistranslation due to mutations in the mitochondrial 12S rRNA was proposed to cause hearing deficits. This study establishes a mouse model for mitochondrial mistranslation based on mutation of the mitoribosomal protein MRPS5, which recapitulates the suggested pathomechanism of the A1555G 12S rRNA mutation.